ECONOMETRIC MODELING BASED ON PANEL DATA - Muminova Maxbuba Abduvafoyevna (European Science Publishing, 2024)
In this article, panel data, analysis, data representing the activities of a set of enterprises by quarters, annual socio-economic indicators of a specific group of countries, the construction of flexible and comprehensive models of panel data, and obtaining answers within the framework of spatial models are examined. The importance of panel data in analyzing the impact of various factors on the development of events over time, and in researching econometric and socio-economic processes, is discussed.
Keywords: panel data, time series, regression model, production functions, production logarithm, identification.